1997
DOI: 10.1097/00003246-199707000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of nitric oxide as contaminant in hospital compressed air

Abstract: The low concentration of nitric oxide in hospital compressed air improves oxygenation in patients with normal lungs receiving mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
2
4
0
1
Order By: Relevance
“…These data extend the findings of our group and others in subjects with normal lungs to include patient groups in whom inhaled NO may be considered as a therapeutic option. Although these increases in PaO 2 are minimal from a clinical perspective, they are consistent with our previous studies in healthy ventilator-dependent adults [13] and children with acute lung injury [23]. Furthermore, as demonstrated in our prior study in children, all the gas exchange changes can be attributed solely to these minimal levels of inhaled NO, in that they were duplicated when NOfree gas at the same FiO 2 (equivalent to our steps A1 and A2) was supplemented with exogenous NO to these very low levels [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These data extend the findings of our group and others in subjects with normal lungs to include patient groups in whom inhaled NO may be considered as a therapeutic option. Although these increases in PaO 2 are minimal from a clinical perspective, they are consistent with our previous studies in healthy ventilator-dependent adults [13] and children with acute lung injury [23]. Furthermore, as demonstrated in our prior study in children, all the gas exchange changes can be attributed solely to these minimal levels of inhaled NO, in that they were duplicated when NOfree gas at the same FiO 2 (equivalent to our steps A1 and A2) was supplemented with exogenous NO to these very low levels [23].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the end-inspiratory and end-expiratory NO levels reached new steady state values within 5 min of changing steps. Furthermore, we [13] and others [1,2,3] have shown that changes in oxygenation in response to changes in inspired NO levels in subjects with hypoxia occur rapidly and tend to remain constant over at least an hour.…”
Section: Study Limitationsmentioning
confidence: 67%
See 1 more Smart Citation
“…Supplementation of NO‐containing nasal air to these patients improves arterial oxygenation and reduces pulmonary vascular resistance (Lundberg et al, 1995c). In addition, Pinsky et al have shown that the hospital pressurized air may contain NO levels similar to those described earlier (6–500 ppb) which may consequently have effects on arterial oxygenation and pulmonary arterial pressure in mechanically ventilated patients (Lee et al, 1997; Pinsky et al, 1997; Lum et al, 1998; Tan et al, 2002). In another study, nostril widening with breathe easy nasal strips improved arterial oxygenation in spontaneously breathing patients, likely by enhancing ventilation through the nasal airways thereby increasing NO delivery from the nasal airways to the lungs (Herulf et al, 1999).…”
Section: No As An “Aerocrine” Messengersupporting
confidence: 56%
“…Hospital compressed air is often contaminated with NO, which effects patients. Levels of 13-79 ppb and 2-550 ppb improve oxygenation in neonates [29] and adults [30], respectively. In a study by MOURGEON et al [15], it was shown that more than half of the maximal effect of inhaled exogenous NO on arterial oxygenation and pulmonary artery pressure in patients with ARDS was achieved at levels of 150 ppb.…”
Section: Inhaled Nitric Oxidementioning
confidence: 97%